2018
DOI: 10.1007/s11102-018-0904-4
|View full text |Cite
|
Sign up to set email alerts
|

The experience with transsphenoidal surgery and its importance to outcomes

Abstract: We conclude that a center with experience of > 25 transsphenoidal operations for pituitary adenomas per year provides a high likelihood of safe TSS. Surgery for CD requires a particularly high level of practice to guarantee excellent remission rates. The endocrinologist has the unique opportunity to audit the surgical success by hormone measurement and to refer patients to neurosurgeons with proven excellence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 128 publications
3
37
0
3
Order By: Relevance
“…The rates of major complications, including postoperative hypopituitarism, intraoperative CSF leakage and transient diabetes insipidus, in our study are similar to those in other studies (43)(44)(45).…”
Section: Resultssupporting
confidence: 91%
“…The rates of major complications, including postoperative hypopituitarism, intraoperative CSF leakage and transient diabetes insipidus, in our study are similar to those in other studies (43)(44)(45).…”
Section: Resultssupporting
confidence: 91%
“…A thorough review of outcomes in persistent versus recurrent CD can be found in Rubinstein et al [ 54 ]. Pituitary surgery should be conducted in a center with high experience (more than 25 surgeries per year [ 55 ])—this applies both for persistent, recurrent, and surgery-naïve CD as well. A second pituitary surgery seems to be currently the first-line therapy in recurrent CD with a mean remission rate of 64%, but high rates of variability (38–90%) is reported in the literature [ 54 ].…”
Section: Treatment Options After Recurrence and In Persistent Cushingmentioning
confidence: 99%
“…This is supported by others. However, in their metaanalysis, rhinological complications were not considered [6]. We expect that by a prospective, comparative multicenter study it will be shown that surgical experience will also have a positive effect on the rate of rhinological complications independent of microsurgical or endoscopic technique.…”
Section: Discussionmentioning
confidence: 99%